Host Plant Variation and Lack of Genetic Differentiation in Populations of Dione (Agraulis) dodona Lamas & Farfán (Lepidoptera: Nymphalidae) - Jackie Farfán; José Cerdeña; Wilson Huanca-Mamani; Héctor A. Vargas; Gislene L. Gonçalves; Gilson R. P. Moreira (Insects, 2022)
Dione (Agraulis) dodona (Nymphalidae: Heliconiinae) is a butterfly restricted to the western slopes of the Andes of Peru and Chile and is associated with Malesherbia tenuifolia in xerophytic environments. In this study, we found six additional species of host plants for D. (A.) dodona belonging to the genus Malesherbia (Passifloraceae). We used mitochondrial DNA sequences (COI) and microsatellites to screen genetic variation and investigate population structure in six geographic disjointed populations of D. (A.) dodona associated with distinct Malesherbia species. The PCoA analysis based on allele frequencies evidenced a lack of differentiation among populations and a low FST. The Bayesian cluster analyses revealed the existence of three genetically distinct groups, but almost all individuals present an admixture ancestry. An absence of isolation by distance pattern was observed. Possible scenarios are discussed: a bottleneck or recent colonization from interconnected populations from the south, and ongoing gene flow among local populations by high dispersal through a landscape formed of isolated populations of Malesherbia.